NANOTOXICITY AT VARIOUS TROPHIC LEVELS: A REVIEW - S. K. RAJKISHORE*, K. S. SUBRAMANIAN, N. NATARAJAN AND K. GUNASEKARAN (The Bioscan, 2013)
Nanotoxicity refers to the physiological and metabolic interruptions caused by engineered nano-particles that may differ at various trophic levels of ecological pyramids. This review focuses on the nanotoxicity events that are reported in literature in a wide array of living organisms such as algae, microbes, plants, fishes, rodents and humans. Literature survey reveals that even adaptive organisms such as algae which have proved to tolerate adverse and fluctuating environmental conditions are prone to nanotoxicity as a result of defective photosynthetic system. The microbes such as plant growth promoting rhizobacteria and other beneficial soil microorganisms have been reported to be inhibited in its functionalities by nanoparticles but their relative toxicities are quite inconclusive and warrant further investigations. Despite plants have evolved tolerance mechanisms to deter xenobiotics, they expressed their sensitivity to some of the nano-particles as a consequence of physical and chemical routes of action. In animal models (rodents), the data have vividly shown that the nanoparticles have caused significant inflammatory effects while in aquatic system (fish) nanoparticles are found to accumulate in various organs besides causing morphological dysfunctions. In the case of humans, nano-particles enter primarily through inhalation which causes inflammation and ultimately cancer. Overall, the nanotoxicity in biological systems is mainly caused by the excessive production of reactive oxygen species that damages the living cells. Despite this mechanism has been unequivocally demonstrated in some case studies, scientists are still working harder to establish a clear relationship between nanoparticles and its toxicity impacts